Modernism Re-enacted: Decolonial Forms of Moving Images and Curatorial Practice in documenta11 (2002) - ANNALISA PELLINO (MIMESIS INTERNATIONAL, 2022)
The essay proposes a reading of Documenta11 (2002) as a “paradigm shifting exhibition” that, within the frame of a globalised art system in the aftermath of September 11, 2001, inaugurated a new discursive approach that overcame the North-Atlantic protocols of curatorial practice. The proposal takes into consideration a theoretical frame that considers postmodernism not as an overcoming of the modernism, but as an internal formation to its plot from a cultural, aesthetic and media perspective. In the wake of the post-colonial and de-colonial critique, the great European exhibition – stemmed within the modernist epistemological framework of 20th Century – dismissed the Western affordances of both modernist and postmodernist approaches. In particular, the essay focuses on Okwui Enwezor’s curatorial choice to restructure the exhibition into a totally new configuration around the black box – in place of the white cube as the epitome of Western modernism – in order to re-enact modernism and affirm new forms of art and curatorial practices oriented by the idea of multiple modernities and temporalities.